Using a digital whiteboard for student engagement in distance education. (July 2021) - Reguera, Elsa Aniela Mendez; Lopez, Mildred
Highlights: Education innovation focuses on creating strategies to nurture active learning spaces. A successful transition built on previous projects and creativity from teachers. Digital whiteboards provide an active interaction space despite COVID19. Building community and a safe-space for students to interact is a lesson learned. Abstract: The COVID-19 pandemic transformed educational processes across different educational levels. As institutions and faculty members effort focused on guaranteeing academic continuity, the challenge was how to translate the learning methodologies applied in the classroom to virtual settings. A digital whiteboard was integrated to synchronous class sessions to complement the educational experience. During these sessions, students and teachers interacted to co-construct ideas and socialize learning. The objective of this study was to assess the impact of introducing a digital whiteboard in student engagement. The quantitative approach integrated student's perception through an online survey with 12 items. The results show that the students enjoyed the dynamic(4.56), students believe that the incorporation of digital whiteboard contributed to understanding abstract concepts(4.83), and perceived the resource contributed for class engagement(4.72). The design of educational projects that incorporate these resources translate to active learning dynamics which foster student engagement. Graphical abstract: Image, graphical abstract